A Reviewing the Top Health Systems with Comparison to Iraqi Health System: Commercial Health Systems Review - Alhiti, Hazim A (Journal of the Faculty of Medicine Baghdad, 2021)
Background: The assessments of performance in any health system is achallenging goal. Objectives: This article reviews the top healthcare systems then comparesthem to Iraqi health system. Patients and methods: The top 12 commercial Health Systems in 2020ranked by a survey of more than 20,000 international citizens from 73countries on 65 diverse metrics. These metrics vary from simple to criticalhealth system performance criteria. Results: Up to January 2020, the review shows that Canada has the top Health System. Most other top countries are Europeans. There are some strong and weak points in each health system. Iraqi health system struggles with several obstacles that need a rehabilitation. Conclusions: Iraqi health system needs some improvements. TheNetherlands Health system model improves the Iraqi health system.